Granulosa cell tumors of the ovary: Do they have any unique ultrasonographic and color Doppler flow features?. Issue 3 (1st May 2001) - Sharony, R.; Aviram, R.; Fishman, A.; Cohen, I.; Altaras, M.; Beyth, Y.; Tepper, R.
Abstract : The aim of this study was to describe the ultrasonographic and Doppler flow attributes of granulosa cell tumors (GCT) of the ovary and to compare these attributes to those of epithelial tumors of the ovary. Among 13, 475 gynecological patients who were scanned in our ultrasound unit between 1992 and 1996, seven patients had GCT. The final diagnosis was confirmed, postoperatively, by pathologic examination and by applying the WHO classification. The ultrasonographic findings of the GCT patients were compared to those recorded in a second group of 29 patients who had been diagnosed with epithelial tumor of the ovary. The sonographic appearance of GCT of the ovary was semi-solid and the endometrium was thick in six of the seven patients. Doppler flow studies of vessels within or in the contour of the lesions showed the resistive index (RI) to be 0.448 ± 0.018. The epithelial tumors had a similar appearance and flow pattern except for the presence of ascites in one-third of the patients. Ultrasound scanning, including color Doppler flow, did not contribute data that could assist in differentiating between GCT and epithelial tumors of the ovary.